2018
DOI: 10.1016/j.celrep.2018.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the FSTL1-DIP2A Axis Improves Anti-tumor Immunity

Abstract: Immune dysfunction is a strong factor in the resistance of cancer to treatment. Blocking immune checkpoint pathways is a promising approach to improve anti-tumor immunity, but the clinical efficacies are still limited. We previously identified follistatin-like 1 (FSTL1) as a determinant of immune dysfunction mediated by mesenchymal stromal/stem cells (MSCs) and immunoregulatory cells. Here, we demonstrate that blocking FSTL1 but not immune checkpoint pathways significantly suppresses cancer progression and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…FSTL1 exerts this effect on migration through the reduction of various cytokines, including metalloproteinase-2 (MMP-2), CCL2, and CXCL12 (Chan et al, 2009). Moreover, FSTL1 is considered a determinant of immune dysfunction mediated by mesenchymal stroma/stem cells (MSCs) and immunoregulatory cells, and may therefore represent a target to suppress cancer progression (Kudo-Saito et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…FSTL1 exerts this effect on migration through the reduction of various cytokines, including metalloproteinase-2 (MMP-2), CCL2, and CXCL12 (Chan et al, 2009). Moreover, FSTL1 is considered a determinant of immune dysfunction mediated by mesenchymal stroma/stem cells (MSCs) and immunoregulatory cells, and may therefore represent a target to suppress cancer progression (Kudo-Saito et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have showed that FSTL1 was involved in tumor develop and tumor immunity by variety of mechanisms, such as promotes metastasis and chemoresistance through NFÎșB-BMP signaling pathway in esophageal squamous cell carcinoma [12], activating the focal adhesion signaling pathway to promotes colorectal cancer [11], causing immune dysfunction in lung cancer [15] and tumor with bone metastasis [32]. From these results, we can speculate that FSTL1 is crucially involved in tumor progression and tumor immunity.…”
Section: Discussionmentioning
confidence: 82%
“…FSTL1 also affects the progression of multiple tumors by modulating the host immune system, leading to immune dysfunction in many cases. FSTL1-induced immune dysfunction leads to tumor bone metastases [14] and activation of immune evasion mechanisms in patients with non-small cell lung cancer (NSCLC) through the FSTL1-DIP2A axis [15]. FSTL1 plays a crucial role in tumor-immune and cancer cell progression.…”
Section: Introductionmentioning
confidence: 99%
“…Yonsei datasets, respectively). FSTL1 was reported as a key mediator in immune dysfunction driven by metastasis and aging in mouse cancer models 48 but no functions of it in gastric cancer was reported previously.…”
Section: Clinical Significance Of the Methylation-driven Key Regulatorsmentioning
confidence: 97%